Prediction of Snyder Synthetic Unit Hydrograph Coefficient for Cidurian Watershed - Zulfa, Graciela Febriyanti; Purnaditya, Ngakan Putu; Wigati, Restu; Subekti, Subekti; Priyambodho, Bambang Adhi (Jurnal Fondasi, 2023)
Watershed management is starting with knowing and recording the problems that exist in the watershed. Condition of the watershed that continues to deteriorate can trigger natural disasters such as flash floods that occurred in the Cidurian Watershed. Hydrological design, especially for short-term phenomena runs generates the synthetic unit hydrograph. Snyder synthetic unit hydrograph is the common synthetic hydrograph that widely used on hydrological analysis. Generally, on the snyder synthetic unit hydrograph, the coefficient value (peak coefficient, time coefficient, CW75 and CW50) is only based on estimates or previous research so that the calculation of discharge is less accurate and needs further research. This study discusses the prediction of the value of the Peak Coefficient (Cp), Time Coefficient (Ct), CW75 and CW50 in the Cidurian Watershed using the Snyder Synthetic Unit Hydrograph (HSS) and get a calculation graph between the Polynomial and Collins Unit Hydrographs against the Snyder Synthetic Unit Hydrograph (HSS) in the Cidurian Watershed with rainfall data processing using the Thiessen Polygon, Mononobe, and Alternating Block Method (ABM). The results showed that the value of Peak Coefficient (Cp) = 0.59, Coefficient of Time (Ct) = 0.09, CW75 = 1.22, CW50 = 2.14, with Peak Discharge (Qp) Collins Measured Unit Hydrograph 19th hour = 1.589 m3/s, and Peak Discharge (Qp) Snyder Synthetic Unit Hydrograph 11th hour, 1 = 1.59 m3/s.